IPTEKS BAGI KEWIRAUSAHAAN MELALUI USAHA SMART BAG PLUS: TAS EDUKATIF SEBAGAI MEDIA INTERAKTIF BELAJAR MATEMATIKA YANG EKONOMIS DAN RAMAH LINGKUNGAN - Pranoto, Aji; Saputri, Widya Andi Karmila (JURNAL GAUNG INFORMATIKA, 2017)
Bags have become complete, both in terms of fashion and the need to store goods during the trip. Bags can also be used as a means of education, especially for mathematics subjects. In addition, the number of schools and colleges adds more and more appropriate if the business of making this smart bag established. Smart bag business is named Smart Bag PlusSmart Bag Plus is designed specifically for children that is PAUD, Kindergarten and Elementary School level as an interactive media of learning mathematics with the concept of playing while learning environmentally friendly. The packaging is as neat as possible, unique, and interesting to further upload people to buy it. With a variety of reasons are expected by the establishment of smart bag business can meet the market share of innovative bags and can be as a means of education. Therefore, it can be concluded that the turnover to be generated from this activity will be appropriate and appropriate estimates so that this business can exist and be able to help the community in learning and fashion.